1995
DOI: 10.1002/jms.1190301110
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of doubly charged organic cations by electrospray ion cyclotron resonance mass spectrometry

Abstract: The production and detection of doubly charged organic cations were studied using a previously unreported approacklectrospray ionization coupled with Fourier transform ion cyclotron resonance mass spectrometry. Owing to its ultra-high mass resolution, accurate and stable mass calibration, multiple stages of collisionally activated dissociation (CAD) allowing tandem mass spectrometry and extremely long ion storage times (> 1 min), this technique has proven to be a powerful method for the detection and study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…This was puzzling, since it had been shown earlier that ESI, as a soft ionisation technique, is an excellent method for transferring intact pyridinium ions into the gas phase. 11 Evidently, during the ESI process, the sample molecules are decomposed, with the formation of [A -H] + ions (Scheme 2).…”
Section: Esi Spectramentioning
confidence: 99%
“…This was puzzling, since it had been shown earlier that ESI, as a soft ionisation technique, is an excellent method for transferring intact pyridinium ions into the gas phase. 11 Evidently, during the ESI process, the sample molecules are decomposed, with the formation of [A -H] + ions (Scheme 2).…”
Section: Esi Spectramentioning
confidence: 99%
“…1 Indeed, they are fundamental in gas-phase ion chemistry and in mass spectrometry in spite of their short lifetime. [2][3][4] They also play important roles in photochemical processes, 5,6 as well as in astrochemistry and the chemistry of the atmospheres. [7][8][9][10] It has also been postulated that they may have played some role in the origin of life, [11][12][13][14][15] since doubly charged metal ions may have induced the precipitation of nucleic acid molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Diquaternary ammonium ions have been used for a variety of biochemical applications, such as herbicides (diquat, paraquat), anti-hypertensive drugs (hexamethonium), and muscle relaxants (decamethonium, succinylcholine, curare alkaloids). Mass spectrometry has been successfully applied to the characterization of such ions using a variety of desorption ionization and spray techniques [1][2][3][4][5][6][7]. For example, Hercules et al [1] used laser desorption to ionize a variety of diquaternary ammonium salts.…”
Section: Introductionmentioning
confidence: 99%
“…Eyler et al [5] recently reported the use of ESI with Fourier transform mass spectrometry (FTMS) [8] to study the dissociation and reactivity of doubly charged pyridinium cations. For these experiments, FTMS has the advantage of long ion storage times and extensive capabilities for tandem MS and MS n .…”
Section: Introductionmentioning
confidence: 99%